Don’t panic (yet): The implications of ChatGPT for Education Studies in the UK - Stephen Dixon (Educational Futures, 2023)
This theoretical article explores the recent furore surrounding the emergence of generative Artificial Intelligence tools, particularly ChatGPT. Both AI and ChatGPT are discussed, before recent debate is contextualised against historical reactions to the adoption of technologies in education. An example generated ‘essay’ is critiqued, before discussing more recent educational responses, and the implications of ChatGPT and other AI tools for Education Studies as an academic discipline, with reference made to the QAA Benchmarks (2019). Amidst calls for the return to more authentic assessment procedures, it is argued that Education Studies is already in a strong position to meet the challenges posed by generative Artificial Intelligence software. Furthermore, it is stressed that we should be critically engaging with these emerging technologies, discussing their ethical implications with students, and exploring their potential as both pedagogical and assistive tools.